A survey on awareness and knowledge of Islamic microfinance in India - Hassan, Rusni; Syed Ahmed, Salman (International Journals of Multidisciplinary Research Academy, 2019)
Microfinance provides financial services to small businesses and poor individuals who lack access to conventional banking. Conventional microfinance institutions have expanded their operations in the last two decades. Among the many factors that were responsible for the microfinance crisis in India, one major factor was the high interest rate which still continues to exist. The giants of Microfinance in India until today are known to be charging high interest rates. Approximately 77% of India‟s population continues to be below poverty line. Moreover, on looking into the population of the financially excluded, the majority of them are Muslims who are of the belief that giving or taking of interest is not permissible. Hence, study on interest free or Islamic microfinance in India can help eradicate poverty not just among Muslims but in India as a whole. This study aims to gauge the awareness and knowledge of Islamic microfinance among the general public of India. The results of this study will help translate into actions in areas needed for in depth penetration and acceptance of Islamic microfinance in India. The paper adopts a Quantitative approach where Questionnaire is distributed online by way of random sampling and 303 responses were received. Data is analyzed using SPSS22 software. The findings show that in general the public is aware of the term Islamic microfinance but with regards to the products and services offered by Islamic microfinance institutes, the level of awareness is very low. This gives an insight to in which direction the attention and efforts are currently needed to raise public awareness of Islamic microfinance.